2020
DOI: 10.1101/2020.02.09.940726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural variation in hippocampal dentations among healthy young adults

Abstract: Little is known about hippocampus dentations -or "bumps" on the inferior surface of the hippocampus -and whether they hold functional significance. Empirical work on these features is beginning to emerge, but no study has yet been conducted in which their spatial positions are demarcated, and their putative role in individual differences in memory is based on a single small study. We gathered ultra-high resolution isotropic MTL scans from young-adult sample and performed such measurements. On the long axis, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Accurately aligning and segmenting the hippocampus across individuals is important in order to provide anatomically meaningful results. However, inter-individual variability in the anterior-posterior curvature and number of digitations of the hippocampus makes alignment and parcellation into subfields a unique challenge (Ding & Van Hoesen, 2015; ten Hove & Poppenk, 2020; DeKraker et al, 2018). The issue of inter-individual variability of the hippocampus is typically solved in one of two ways.…”
Section: Discussionmentioning
confidence: 99%
“…Accurately aligning and segmenting the hippocampus across individuals is important in order to provide anatomically meaningful results. However, inter-individual variability in the anterior-posterior curvature and number of digitations of the hippocampus makes alignment and parcellation into subfields a unique challenge (Ding & Van Hoesen, 2015; ten Hove & Poppenk, 2020; DeKraker et al, 2018). The issue of inter-individual variability of the hippocampus is typically solved in one of two ways.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it may be that no associations with NPT measures exist and the previous studies were false positives. The latter is unlikely given that two separate studies using different methods from two cohorts (Beattie et al, 2017 ; Kilpattu Ramaniharan et al, 2022 ) as well as in two unpublished reports from other labs (Parpura et al, 2022 ; ten Hove & Poppenk, 2020 ) did show correlations with memory.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that the variability of HD (from quite bumpy to totally smooth hippocampi) is positively correlated with measures of memory performance, specifically verbal memory recall and visual memory recognition (Beattie et al, 2017 ). A study of medial temporal lobe scans found that HD was associated with visual source memory, but not recognition memory (ten Hove & Poppenk, 2020 ). Another study by our group on healthy children and adolescents showed that HD was positively associated with age, with older adolescents having a wide range of dentation similar to adults, while younger children had few dentes or exhibited no visible dentation (Beattie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only recently have these features become apparent using 3D neuroimaging such as ultra-high-resolution in vivo and ex vivo MRI. These methods have begun to reveal wide interindividual variability in the anterior-posterior curvature of the hippocampus and in the presence and prevalence of digitations (Figure 2) [11,[15][16][17]. Early evidence suggests that the extent of digitation is linked to healthy aging [16] and memory [17].…”
Section: Relevant Anatomymentioning
confidence: 99%
“…This can readily be appreciated by comparing coronal slices with multiplanar slices in Figure 1. In addition, there is broad interindividual variability in the number and magnitude of digitations within the hippocampal head [11,20] as well as the hippocampal body and tail [15][16][17] (Figure 2). Digitations include the SRLM, and thus it is not yet clear whether geometric rules derived from the SRLM remain stable across variants with different digitation patterns.…”
Section: Trends Trends In In Neurosciences Neurosciencesmentioning
confidence: 99%